Efektivitas Launchgood Sebagai Media Crowdfunding Dana Sosial dalam Perspektif Hukum Islam - Setya Indrawanto (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2025)
The presence of today's online platforms is quite easy for the community as a field to help and donate without having to meet in person, just via online. As we all know, in Indonesia there are several online platforms that move for the prosperity of people in need. For example, such as platforms we can, charity, good seeds, online alms, poor wallets and several others. Some people do not believe that the donated funds will be used properly. Not only in Indonesia, now abroad also make several online platforms such as Launchgood, which also have a function to make it easier for people in the world to help each other our brothers and sisters, our brothers and sisters, our friends out there who need it and who will later be distributed to those who are right. Based on the background of the problem, questions arise about how people or donors can donate through the launchgood platform and how effective launchgood.com as a medium of crowdfunding social funds from the perspective of Islamic law. In starting this crowdfunding, we conducted this research using a qualitative research type and using an interpretive paradigm. Where this stage focuses on observation of content analysis.